Analysis on the emission and potential application of Cherenkov radiation in boron neutron capture therapy: A Monte Carlo simulation study. (July 2018) - Shu, Di-Yun; Geng, Chang-Ran; Tang, Xiao-Bin; Gong, Chun-Hui; Shao, Wen-Cheng; Ai, Yao
Abstract: This paper was aimed to explore the physics of Cherenkov radiation and its potential application in boron neutron capture therapy (BNCT). The Monte Carlo toolkit Geant4 was used to simulate the interaction between the epithermal neutron beam and the phantom containing boron-10. Results showed that Cherenkov photons can only be generated from secondary charged particles of gamma rays in BNCT, in which the 2.223 MeV prompt gamma rays are the main contributor. The number of Cherenkov photons per unit mass generated in the measurement region decreases linearly with the increase of boron concentration in both water and tissue phantom. The work presented the fundamental basis for applications of Cherenkov radiation in BNCT. Highlights: Emission of Cherenkov photons in boron neutron capture therapy (BNCT) was explored. Cherenkov photons are generated from secondary charged particles of gamma in BNCT. Linear relation between boron concentration and Cherenkov photons was investigated. It presented the fundamental basis for applications of Cherenkov radiation in BNCT.